Children’s Dignity and Equality in Family Life - PIETRZAK, HELENA (Prawo Kanoniczne, 2019)
The dignity and equality mentioned in the title include a wide range of interdisciplinary considerations (based on the international, constitutional, civil or criminal law). This analysis focuses on their subjects (children) who – just like adults, regardless of their features of character or level of mental and physical development – are entitled to certain rights and liberties (human rights) whose source is none other than dignity. Is children's dignity equal to that of adults? Based on the applicable legal regulations, it is; however, in practice, in the context of "certain actions" of various adults, it may not always be so. Several currently occurring "non-legal actions", including criminal ones – diminishing children's dignity and turning them into "objects" at the disposal of persons in control (parents, guardians, intermediaries) – have been presented. The study concentrates on the following three aspects: (i) direct influence on family legislation (by commercial use of genetic material); (ii) human trafficking (except adoption); and (iii) assessment of the recognition of children's dignity in respect of custody (any attempts at appropriation, enslavement, violence or maltreatment whereby children become instruments of adults' aspirations).